2018
DOI: 10.1136/jim-2017-000525
|View full text |Cite
|
Sign up to set email alerts
|

A New Predictor of Atrial Fibrillation after Coronary Artery Bypass Graft Surgery: Hatch Score

Abstract: The aim of this study was to investigate the association between HATCH score and atrial fibrillation (AF) after coronary artery bypass graft (CABG) surgery. 369 patients (103 patients with AF and 266 patients without AF) undergoing isolated CABG surgery were analyzed. Complete medical records were retrospectively collected to investigate HATCH score. The median age of patients with AF was significantly higher than the median age of non-AF group (60.8±10.0 years vs 67.8±9.5 years, P<0.001). HATCH score was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…They also found that a HATCH score >2 indicated possible PoAF with 72% sensitivity and 75% specificity [8]. A study by Selvi et al [27] included 369 patients who underwent CABG and detected PoAF in 27.9% of the patients; the patients were categorized as PoAF+ and PoAF–. HATCH score and age were significantly higher in the PoAF+ group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that a HATCH score >2 indicated possible PoAF with 72% sensitivity and 75% specificity [8]. A study by Selvi et al [27] included 369 patients who underwent CABG and detected PoAF in 27.9% of the patients; the patients were categorized as PoAF+ and PoAF–. HATCH score and age were significantly higher in the PoAF+ group.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, HATCH score and higher triglyceride levels were found to be independent predictors of PoAF. In ROC curve analysis, a HATCH score >2 indicated possible PoAF with 42% sensitivity and 70% specificity [27].…”
Section: Discussionmentioning
confidence: 99%
“…The HATCH score is a scoring system containing 5 different variables that play a role in the etiology of atrial fibrillation (AF) (Table 1). It is used in cardiology clinics to demonstrate AF recurrence after radiofrequency ablation and shown to predict the development of PoAF after CABG operations with cardiopulmonary bypass (CPB) [Miao 2012;Selvi 2017].…”
Section: Introductionmentioning
confidence: 99%
“…AF developed in 27.9% of the patients and the HATCH score was an independent predictor for PoAF. In the ROC curve analysis, HATCH score >1 was predictive for POAF with 42% sensitivity and 70% specificity [ 21 ]. Another study was conducted by Emren et al including 284 CABG patients.…”
Section: Discussionmentioning
confidence: 99%